Prinsip Komunikasi Islam dalam Novel Para Pencari Keadilan - Fahmi, Lukman (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2019)
The primary purpose of communication is to change the mindset of humans or spreading influence on one's beliefs, whether in the religious, political, social to the business. This article discusses how the principles of Islamic communication are presented in the character of Rumondang Siregar as the main character in the novel Para Pencari Keadilan. Using a descriptive qualitative design, the study has found that the main character of the novel, Rumondang, is able to influence other figures to embrace Islam. This is represented by inserting Islamic values in each paragraph of the novel and dialogue that uses the principles of Islamic communication, namely qaulan maysura, qaulan karina, qaulan layina, and qaulan ma’rufa.